Socio-Ecological Analysis of Andesite Mining Plans in Wadas Village, Purworejo, Central Java - Kismunthofiah, Kismunthofiah; Masyitoh, Dewi; Hidayatullah, Ahmad Fauzan; Safitri, Ririh Megah (UI Scholars Hub, 2021)
The management of natural resources based on local wisdom has become a crucial issue lately. Mainstreaming local values and norms is one of the best practices in managing community resources and can minimize social conf licts. However, the fact that the practice of managing natural resources often has an impact on the emergence of conf lict and community unrest over environmental degradation. As is the case in Wadas Village which became the location of andesite stone mining as material for the construction of the Bener Dam. Environmental degradation arising from the practice of andesite rock mining also has an impact on socio-ecological contexts. The study aims to analyze Wadas cases and the ecological social impacts they cause. Descriptive qualitative research methods are used to string together analyses related to the socio-ecological impact on risk-management mining practices. Data related to the mining process, management of mine sites, and socio-ecological impacts are obtained through in-depth observations and interviews. This article states that andesite rock mining causes environmental degradation and decreased quality of life of people that have the potential to have socio-ecological impacts.This study is expected to be a feasibility review material in the context of the determination of mining areas and development programs that will be carried out by the government and related stakeholders.